Pemanfaatan Limbah Cangkang Kelapa Sawit Kombinasi dengan Ekstrak Etanol Lidah Buaya sebagai Agen Antibakteri - ratna kurniati; Raisa Masevani; Jelita Syandia Fitri; Annisyah Aulia Dicken; Deri Islami (JURNAL FARMASI DAN MAKANAN, 2023)
The enormous potential for producing palm oil shell waste can be utilized as an effort to reduce palm oil waste, namely by processing palm kernel shells into activated charcoal combined with ethanol extract of aloe vera as an antibacterial product. The aim of this research is to actively test palm oil shells in combination with aloe vera extract against the growth of Staphylococcus aureus and Escherichia coli bacteria as natural antibacterials. The concentrations of activated charcoal and aloe vera ethanol extract are 0%:100%, 0%:50%. 100%:0%, 50%:0%, 50%:50%, 25%:25%, 30%:70%, 15%:35% and cream concentrations of 10% and 20%. The research method used an antibacterial testing method, namely the agar diffusion method with the positive control amoxicillin. The data obtained were analyzed using a completely randomized design and continued with the DMRT test at a 95% confidence interval. The results of this study show that there is great antibacterial activity in the combination of activated charcoal and aloe vera extract with a ratio of 15%:35% with an inhibition zone of 18.25 mm in Escherichia coli bacteria and 15.07 mm.